Obowiązek oparty na preferencji - Drofiszyn, Marcin (Filozofia Nauki, 2022)
The paper presents a formalization of Henryk Elzenberg’s system of axiology, which features the notions of value, ought, and obligation. The formalization I propose is constructed in the language of sentential modal logic. However, as Elzenberg was well aware, his system of axiology had several difficulties. To avoid them, I propose a modification of the system’s foundations and show that it preserves the formal properties of ought and obligation postulated by Elzenberg. To show this, I express in the proposed formal language a certain theory of the logic of preference that I describe from the syntactical as well as the semantical point of view.